Recommendations for Overcoming Difficulties in Video Assisted Thoracoscopic Pericardial Fenestration - Selçuk GÜRZ; Serkan Burç DEŞER; Necmiye Gül TEMEL (Ahi Evran Medical Journal, 2022)
Purpose: Pericardial fenestration is used to treat recurrent pericardial effusion. This study aimed to assess the issues and solutions in pericardio-pleural fenestration (PPF) applications using video-assisted thoracoscopic surgery (VATS), which is more prominent today.